Chromosomal aberrations as etiological factors of intrauterine growth retardation - Petrović Bojana; Ljubić Aleksandar; Nikolić Ljubinka (Vojnosanitetski Pregled)
Background/Aim. Intrauterine growth retardation (IUGR) is a pathological condition of pregnancy characterised by birth weight below the 10th centile. A number of fetal, placental and maternal causes can lead to IUGR; although, in most cases no specific causes can be identified. The aim of this study was to determine the part of chromosomal abnormalities in IUGR etiology. Methods. Fetal blood karyotype taken by cordocentesis from 168 fetuses with diagnosed IUGR was analyzed. Results. Chromosomal rearrangements both numerical and structural were detected in 14 cases (12.2%). Two cases were triploid. Patau syndrome, Edwards syndrome and Down syndrome were found in two cases each. There was one case of trisomy 7 (47, XY, +7) and one case of trisomy 16 (47, XX, +16); one translocation, 46, XY, t (2; 14)(q23; q32) and a deletion 46, XYdel (12) (p12) as well as two cases of sex chromosomes abnormalities, 45, X (Turner syndrome) and 47, XYY. Conclusion. These findings suggest that a consistent number of symmetrical IUGR cases (about 12%) can be associated with chromosomal rearrangements. Chromosomal aberrations that cause IUGR are heterogeneous, aberration of autosomes, mostly autosomal trisomies, being the most common.